LEITURA DIDÁTICA DA CIDADE DE IJUÍ, RS, PELA EXPOSIÇÃO ITINERANTE - DIVERSIDADE URBANA: A CIDADE DE IJUÍ - 1890-2010 - Bado, Sandra R. d. L.; Atkinson, Célia C.; Walker, Gilmar A.; Stefanello, Belair; Gass, Sidnei L. B.; Azambuja, Bernadete M. d. (Salão do Conhecimento, 2013)
Resumo